Instillation Of Character Values Through Peat Music Gambus at Islamic Boarding School al-Qurán al-Falah Cicalengka Bandung - Rifki Nasrul Hakim; Fitria Rahma Ramadhani; Samsul Susilawati (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
One of the arts in the field of music which is called gambus is one of the arts that can be used as a tool in the struggle for da'wah because in this art Islamic values can be included through the choice of poetry, the chosen intonation, and the composition of the notes. All parts that are included in the art particle play a very important role in this art, both in the world of da'wah and the world of art. In the Islamic community, gambus music can be easily accepted because this work of art has Islamic content and can also increase the level of a servant's love for his god.The type of research used in this writing is an assessment with a qualitative descriptive method using data collection methods through observation, interviews and documentation. By means of analysis, namely reducing the data obtained in the field and then presenting it in the form of a narrative which will finally draw conclusions from the data in the field. The results of this study indicate: (1) The background of gambus music at the Al-Qur'an Al-Falah Islamic Boarding School is to maintain the existence of Islamic art which is starting to fade, then the students are equipped and instilled with a sense of love for Islamic art, especially gambus music. (2) Living Islamic religious values through Gambus music at the Al-Qur'an Al-Falah Islamic Boarding School is quite optimal, this is evidenced by the holding of gambus music at the Al-Qur'an Al-Falah Islamic Boarding School the students are equipped to instill the love for Islamic art, especially stringed music, is then recited and internalized from every verse learned. Because from each content of the poem there are messages about maddah poetry (praise to the prophet), munajat poetry (prayer) and mahabbah poetry (love). (3) The impact of gambus music is very positive on the students. This is evidenced by the results of the research, namely the gambus music activity program aims to channel interests, talents and develop the potential of the students to increase intelligence and become students with chaaracter.